On-site and nearby electricity production potential in Latvia and Czechia - Borodinecs, Anatolijs; Skandalos, Nikolaos; Lebedeva, Kristina; Odineca, Tatjana (International Conference “Environmental Engineering”, 2023)
This study provides an overview of current situation and policy planning documents for the implementation of Renewable Energy Sources [RES] in Latvia and Czechia. The main aim is to evaluate the gathered experience in each country in the use of photovoltaics [PV] for electricity production and to define the possible potential of using PV for achieving the EU’s energy and climate goals for 2030. Czechia has already long-term experience in instating of on-site PV systems, the growth of which remained stagnant since 2013. On the other hand, Latvia faced a significant PV-installation increase since spring 2022. Special attention is paid to both countries’ climate analysis, it is a very similar in solar radiation data. Paper provides data of newest support mechanisms, energy policy documents and marketing models which can be applied for a new PV power plant projects in Latvia and Czechia. The article analyzed the data on dynamics of electricity production, consumption and share of PV electricity in both countries for last ten years. The National Energy and Climate Plans [NECPs] for 2021–2030 and the proposed scenarios for achieving the set goals in the field of energy and climate, regarding increasing the use of RES in electricity generation were also studied. Finally, based on all the analyzed data, it can be concluded that both countries have the on-site and nearby electricity production PV potential to achieve their goals in field of RES electricity generation.